INTERPERSONAL METADISCOURSE IN THE JAKARTA POST E-NEWS OPINION ARTICLES - Bayu Permana Sukma; Dhafid Wahyu Utomo (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2016)
This study discussed about types and functions of interpersonal metadiscourse markers in newspaper article opinion. Interpersonal metadiscourse holds significant role in writing, especially in opinion article, since it reflects writer’s position towards both the content of text and reader. The method used in this study is descriptive qualitative, and the data are taken from opinion articles in The Jakarta Post online, an Indonesian English newspaper. The results of the study suggest that the types of interpersonal metadiscourse markers, such as hedges, certainty markers, attributors, attitude markers, and commentaries are used in the opinion articles. . The results also reveal that the types of markers hold some specific functions in the texts. Hedges help the writers withhold their opinion, while certainty markers function to emphasize it. Attributors function to support the writers’ arguments and attitude markers express their attitudes towards the text and readers. Finally, commentaries help them to build relationship with their readers.